ENHANCING BACTERIAL PHYSIOLOGY EDUCATION: A MIXED-METHODS STUDY ON THE IMPACT OF GAMIFICATION AND YOUTUBE-BASED INSTRUCTION - Mat Jalil, Mohd Taufiq; Zakaria, Nurul Aili; Yunus, Norfatimah Mohamed (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Bacterial physiology is a crucial component of microbiology education, but its abstract and complex content often leads to student disengagement and poor academic performance. Traditional lecture-based methods frequently fail to promote active participation or conceptual clarity. This study investigates the impact of combining gamification and YouTube-assisted teaching strategies on student engagement, understanding, and academic achievement in a bacterial physiology course. Using a mixed-methods design, data were collected from 136 undergraduate microbiology students through structured questionnaires and open-ended responses. Quantitative findings revealed strong student support for both gamified and video-enhanced learning approaches, with high agreement on improvements in motivation, engagement, conceptual understanding, and exam preparedness. Qualitative responses highlighted the benefits of visual content, including its motivational effect, interactivity, and immediate feedback, although some challenges, such as internet access and time constraints, were also noted. The integration of gamification and YouTube was found to align well with contemporary educational theories that emphasize active and multimedia learning. These methods enhanced both cognitive outcomes and emotional engagement, fostering deeper understanding and learner autonomy. Overall, the study supports the value of incorporating gamified and multimedia strategies into microbiology education to better meet diverse learning needs and improve academic success.